Diversity, distribution and abundance of plant species in Bangladesh Agricultural University campus - Mustaina, Z; Islam, MA; Farukh, MA; Biswas, P (Progressive Agriculture, 2021)
The study was conducted on distribution, abundance and diversity of plant species of Bangladesh Agricultural University (BAU), Mymensingh. To conduct the experiment, 20 sampling sites were selected randomly within the study area having an area of 3 square meter and all the plants of various genera and species within the sampling sites were identified. A total number of 9140 plants of 36 species belonging to 28 families were recorded from all the sampling sites among which Axonopus compressus species was identified at the highest number (2755) whereas the species of Borassus flabellifer, Prunus avium, Saracaasoca, Lagerstroemia speciosa, Cassia fistula and Acacia catechu were found at the lowest (01). In case of relative abundance, the percentage was found approximately 30.14% for Axonopus compressus whereas for each of Borassus flabellifer, Prunus avium, Saracaasoca, Lagerstroemia speciosa, Cassia fistula and Acacia catechu it comprises only 0.01% within the total plant species. Considering the habits of the plants, in case of tree species Swietenia macrophylla showed a relatively high abundance (0.175%) and Borassus flabellifer showed the low (0.01%) whereas among the herb Axonopus compressus (30.14%) was found at the highest and Centellaasiatica (0.005%) was at the lowest in terms of abundance. The diversity indexes also revealed that the highest diversity of the plants was observed in the BINA quarter having a value of 0.763 and the lowest was observed in front of the Agronomy faculty (0.018) among the twenty sampling sites. These results emphasized the importance of furthermore and a wide variety study on the plant species within this study area. Progressive Agriculture 32 (1): 22-30, 2021